2013
DOI: 10.1103/physrevc.87.044326
|View full text |Cite
|
Sign up to set email alerts
|

Universal properties of infrared oscillator basis extrapolations

Abstract: Recent work has shown that a finite harmonic oscillator basis in nuclear many-body calculations effectively imposes a hard-wall boundary condition in coordinate space, motivating infrared extrapolation formulas for the energy and other observables. Here we further refine these formulas by studying two-body models and the deuteron. We accurately determine the box size as a function of the model space parameters, and compute scattering phase shifts in the harmonic oscillator basis. We show that the energy shift … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
191
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(201 citation statements)
references
References 33 publications
10
191
0
Order By: Relevance
“…Clearly, the data points do not fall on a single line for either nucleus, and similar results are found for 22 O. Earlier studies [20] showed that the smoothness of E(L), when plotted for a large set of N and Ω values for which UV corrections are small, is a sensitive diagnostic of the quality of L(N, Ω). Thus, L = L 2 is not the accurate box size of the harmonic oscillator basis for fermionic many-body systems.…”
Section: Infrared Cutoffs Of the Oscillator Basissupporting
confidence: 74%
See 1 more Smart Citation
“…Clearly, the data points do not fall on a single line for either nucleus, and similar results are found for 22 O. Earlier studies [20] showed that the smoothness of E(L), when plotted for a large set of N and Ω values for which UV corrections are small, is a sensitive diagnostic of the quality of L(N, Ω). Thus, L = L 2 is not the accurate box size of the harmonic oscillator basis for fermionic many-body systems.…”
Section: Infrared Cutoffs Of the Oscillator Basissupporting
confidence: 74%
“…20 of Ref. [20] as an example. We note that all solid data points employed in the IR extrapolation in Fig.…”
Section: Extrapolations and The Coupled-cluster Methodsmentioning
confidence: 96%
“…While progress toward a theoretically founded understanding of universal infrared extrapolations has been made [103], the ultraviolet situation is less clear. The SRG offers a tool for studying ultraviolet extrapolations, including suggestive but as yet unexplained scaling with the SRG flow parameter [102].…”
Section: Other Applications and Future Directionsmentioning
confidence: 99%
“…While mature techniques to extrapolate results to infinite HO bases are available [142][143][144][145][146][147][148], we limit ourselves to finite bases here, using sufficiently large e max values to eliminate the single-particle basis truncation as a relevant source of uncertainty, typically up to e max = 14 (15 major HO shells). An additional truncation is necessary to manage the enormous memory requirements of 3N interaction matrix elements.…”
Section: Interactions and Implementationmentioning
confidence: 99%